Application of Diffusion Kurtosis Imaging in Evaluating Acute Xerostomia in Nasopharyngeal Carcinoma Treated With Induction Chemotherapy Plus Concurrent Chemoradiotherapy - Zhao, Da-Wei; Fang, Xue-Mei; Zhou, Shu-Han; Luo, Yan-Rong; Wei, Jian; Liu, Kun; Meng, Ling-Ling; Liu, Gang; Li, Jin-Feng; Zang, Xiao; Li, Meng; Qiang, Xiao-Fei; et al. (Frontiers in Oncology, 2022)
Purpose: To identify the efficacy of diffusion kurtosis imaging (DKI) in tracking and monitoring the dynamic change of parotid glands (PG), submandibular glands (SMG), sublingual glands (SLG), and acute xerostomia in nasopharyngeal carcinoma (NPC) patients treated by induction chemotherapy (IC) plus concurrent chemoradiotherapy (CCRT). Methods: The prospective study recruited 42 participants treated by IC+CCRT. All patients underwent six times of DKI scans before IC, before RT, in the middle of the RT course, immediately after RT, 1- and 3-months post-RT. Mean diffusion coefficient (MD) and mean kurtosis (MK) of PG, SMG, SLG, saliva flow rate measured under resting (uSFR) and stimulated condition (sSFR), and xerostomia questionnaire (XQ) scores were recorded. Results: At each time point, sSFR was significantly higher than uSFR (p<0.05 for all). MD of the salivary glands and XQ scores increased over time while MK, uSFR, and sSFR decreased. After IC, the significant differences were detected in MD and MK of bilateral SMG and MK of left SLG (p<0.05 for all), but not in MD and MK of PG, uSFR, sSFR, and XQ scores. After RT, sSFR at 1m-RT decreased significantly (p=0.03) while no significant differences were detected in uSFR and XQ scores. Moderate-strong correlations were detected in MD-PG-R%, MK-PG-R%, MD-PG-L%, MK-PG-L%, MD-SMG-R%, MK-SMG-R%, MD-SMG-L%, MK-SMG-L% and MD-SLG-R%, with correlation coefficients (p<0.05 for all) ranging from 0.401 to 0.714. uSFR% was correlated with MD-SMG% (p=0.01,r=-0.39)、MD-SLG%(p<0.001,r=-0.532)、MK-SMG% (p<0.001,r=-0.493). sSFR% correlated with MD-PG% (p=0.001,r=-0.509), MD-SMG%(p=0.015,r=-0.221), MK-PG% (p<0.001,r=0.524). XQ% was only correlated with MK-PG% (p=0.004,r=0.433). Conclusion: DKI is a promising tool for tracking and monitoring the acute damage of PG, SMG, and SLG induced by IC+CCRT in NPC patients.